IMPLEMENTASI BIMBINGAN KONSELING OLEH GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU ATSAQIBIYAH KOTA BONTANG KALIMANTAN TIMUR TAHUN PELAJARAN 2024/2025 - Nuruddin Kahfi; Rohmatullah; Sri lestari (UNISAN JURNAL, 2026)
This study aims to examine the implementation of counseling conducted by Islamic Education (PAI) teachers in fostering students’ morals at SMP Islam Terpadu AtsaQibiyah, Bontang City, East Kalimantan, in the 2024/2025 academic year. The study is motivated by the importance of moral development as part of character education, shaping students’ behavior according to Islamic values. This research employs a qualitative descriptive approach. Data were collected through observation of counseling activities, in-depth interviews with PAI teachers, and documentation of counseling programs. The results show that PAI teachers implement counseling systematically and structured through guidance, individual approaches, group discussions, and providing advice tailored to students’ situations. This implementation effectively enhances students’ awareness of good behavior, discipline, responsibility, and social skills aligned with Islamic moral values. The study concludes that counseling by PAI teachers plays a crucial role in moral development and is an effective strategy for shaping Islamic character in schools.